Financial equilibrium with career concerns - Andrea Prat; Amil Dasgupta (Theoretical Economics, 2006)
What are the equilibrium features of a financial market where a sizeable proportion of traders face reputational concerns? This question is central to our understanding of financial markets, which are increasingly dominated by institutional investors. We construct a model of delegated portfolio management that captures key features of the US mutual fund industry and embed it in an asset pricing framework. We thus provide a formal model of financial equilibrium with career concerned agents. Fund managers differ in their ability to understand market fundamentals, and in every period investors choose a fund. In equilibrium, the presence of career concerns induces uninformed fund managers to churn, i.e., to engage in trading even when they face a negative expected return. Churners act as noise traders and enhance the level of trading volume. The equilibrium relationship between fund return and net fund flows displays a skewed shape that is consistent with stylized facts. The robustness of our core results is probed from several angles.
Keywords: G0; C7; 330; Career concerns; financial equilibrium; trade volume